2021
DOI: 10.1136/bmjno-2021-000177
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 90-day modified Rankin Scale score with discharge information in acute ischaemic stroke patients following treatment

Abstract: ObjectivesTo understand variability in modified Rankin Scale scores from discharge to 90 days in acute ischaemic stroke patients following treatment, and examine prediction of 90-day modified Rankin Scale score by using discharge modified Rankin Scale and discharge disposition.Materials and methodsRetrospective analysis of acute ischaemic stroke patients following treatment was performed from January 2016 to March 2020. Data collection included demographic and clinical characteristics and outcomes data (modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…In a different cohort of ischemic stroke patients, the change in mRS between day 90 and 1 year ranged between 36 and 41% with a counterbalanced number of mRS improvements and declines [54]. For the same cohort of ischemic patients, a different study has shown that discharge mRS is a good predictor of 90-day mRS [49]. There are more cases and studies to report of course; but, it is fairly universally accepted that most patients remain at the same mRS value from one timepoint to the next [53] and thus values at discharge, although not definitive, should be treated as one critical and reliable indication of longterm outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a different cohort of ischemic stroke patients, the change in mRS between day 90 and 1 year ranged between 36 and 41% with a counterbalanced number of mRS improvements and declines [54]. For the same cohort of ischemic patients, a different study has shown that discharge mRS is a good predictor of 90-day mRS [49]. There are more cases and studies to report of course; but, it is fairly universally accepted that most patients remain at the same mRS value from one timepoint to the next [53] and thus values at discharge, although not definitive, should be treated as one critical and reliable indication of longterm outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…According to Pérez and Tilley [47] it is "the most commonly used outcome measure" in stroke trial. It comprises 7 grades of severity ranging from zero (no symptoms) to five (severe disability) and six (death) and is often dichotomized as good versus poor outcome [48,49]. The fact that mRS administration does not require any specialized equipment or formal training results in a wide range of reported reliability, but is generally enhanced with training and multiple raters [50,51].…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 21 Moreover, many patients discharged with an mRS score of 3 improve to an mRS of 1 to 2 by 90 days poststroke. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Second, the local context prevented extensive ancillary investigations or even the full stroke work-up to determine stroke etiology in most patients. Therefore, inflammatory markers, stroke subtypes, and eventual cardiac structural anomalies could not be included in the predictive model despite the described association between those factors and stroke functional outcomes 18 , 54 , 62 . Finally, despite the large cohort and the fact that the clinical characteristics of our population meet those of other cohorts in SSA, it is possible, even if unlikely, that our results correspond to a local snapshot and may be generalizable to other similar contexts in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke was defined according to the WHO definition 56 . Stroke severity was graded with the NIHSS and stroke outcome was based on the modified Rankin Scale (mRS) 57 at hospital discharge 54 , 58 . Favorable stroke outcome was defined as mRS 0–2 59 .…”
Section: Methodsmentioning
confidence: 99%